A p-type organic semiconductor and a method for preparing the same

CN123022098APending Publication Date: 2026-10-30SHAANXI JIANENG FLEXIBLE THERMOELECTRIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510545413.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]针对现有技术中存在的问题,本发明提供一种P型有机半导体及其制备方法,从而解决现有技术中通过提高掺杂剂的EA在提高聚合物导电性的同时导致有机聚合物半导体稳定性以及防水性下降的技术问题

Benefits of technology

[0021]本发明提出了一种P型有机半导体的制备方法,该方法在传统的二元掺杂体系,即有机半导体+掺杂剂,体系中,加入添加剂进行掺杂反应,在掺杂反应中,通过电子亲合能以及电离电位对掺杂剂、添加剂以及有机半导体进行筛选,使得反应的ΔG2<0,且ΔG3<0;其中,ΔG2为所述添加剂与掺杂剂的反应中间体反应时的吉布斯自由能变化值,ΔG3为总反应的吉布斯自由能变化值。在反应中,添加剂可与掺杂剂的反应中间体反应,稳定掺杂剂的中间体反应,使得反应的ΔG2<0,使得反应的总吉布斯自由能变化值小于0,促进反应的正向进行,在该过程中,定义所述有机半导体与掺杂剂反应的吉布斯自由能变化值为ΔG1,若有机半导体与掺杂剂的反应为自发反应,即ΔG1<0,则在ΔG2的影响下,得到更小的ΔG3,即反应更加充分的向正向进行,另外,如果反应的ΔG1大于0,则在ΔG2的影响下,得到小于0的ΔG3,使得一个热力学上无法进行的反应,转变为热力学上的自发反应,使得反应正向进行,提高了生成物的浓度。本发明通过添加剂的引入,调控反应中间过程,稳定了掺杂剂反应中间体,使得生成物的体系更加稳定,反应充分的正向进行,这种策略不仅避免了高EA掺杂剂的不稳定性问题,还通过多组分协同效应提升了掺杂效率,为高性能有机电子器件的设计提供了新思路。本发明中的P型有机半导体在有机P型热电材料以及电致变色器件制备中均展现出优异的性能,具有广泛的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022098A_ABST
    Figure CN123022098A_ABST
Patent Text Reader

Abstract

The application discloses a P-type organic semiconductor and a preparation method thereof. The preparation method comprises the following steps: mixing an organic semiconductor solution, a dopant solution and an additive solution, and then performing a doping reaction in a nitrogen atmosphere at room temperature to obtain the P-type organic semiconductor. By introducing the additive, the intermediate process is controlled, the intermediate stability and the reaction path optimization are realized, and the forward reaction of the doping reaction process is more complete. The strategy not only avoids the instability problem of the high-EA dopant, but also improves the doping efficiency through the multi-component synergistic effect, thereby providing a new idea for the design of high-performance organic electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic conductive polymer technology, and relates to a p-type organic semiconductor and its preparation method. Background Technology

[0002] Solution-processable high-performance conductive polymer semiconductors refer to a class of polymer materials with excellent conductivity that can be formed into films or patterned through solution processing methods (such as spin coating, inkjet printing, printing, etc.). High-performance conductive polymer semiconductors are currently widely used in the field of flexible electronics, including but not limited to organic thermoelectric devices, organic photovoltaic cells, organic field-effect transistors, organic polymer light-emitting diodes, and organic electrochromic devices.

[0003] Polymers can have their conductivity effectively improved through doping and other treatments. Therefore, for decades, numerous research institutions have been exploring new doping methods to improve doping efficiency and thus enhance the conductivity of these polymer semiconductors. The conductivity of polymer semiconductors under international standards is defined as σ = neμ, where σ is the conductivity, n is the carrier concentration, e is the elementary charge, and μ is the carrier mobility. This definition shows that the conductivity of polymer semiconductors is mainly determined by the carrier concentration (n) and carrier mobility (μ). However, although the carrier mobility of many polymer semiconductors has been significantly improved to exceed 10 cm⁻¹, [further details are needed]. 2 V -1 S -1 (Nature Materials 19, 491-502 (2020); Journal of the American Chemical Society 135, 14896-14899 (2013); Nature Materials 12, 665-671 (2013)). However, the conductivity of the thin films prepared by this polymer semiconductor is still low. Therefore, it is crucial to further improve the carrier concentration of the polymer semiconductor, which usually depends on the efficiency of charge carrier generation during the doping process. Therefore, exploring new doping methods to improve doping efficiency remains a hot research topic in the preparation of highly conductive polymer semiconductors.

[0004] Redox molecular doping is a widely used chemical doping method for preparing highly conductive polymers. The doping process relies on the carriers generated by electron transfer between the polymer and the dopant. Several factors, including the filler in the polymer backbone and the contact interfaces in the device, affect this process. However, the driving force for electron transfer during doping is the matching of the electron affinity (EA) of the dopant in the polymer doping system with the ionization potential (IP) of the organic semiconductor, conforming to Marcus theory (Angewandte Chemie International Edition in English 32, 1111-1121, 1993). To obtain effective p-type doping, the EA of the dopant must match or exceed the IP of the organic semiconductor; in some cases, the EA of the dopant must even be about 0.11 eV higher than the IP of the organic semiconductor to produce effective p-doping and effectively transfer electrons from the organic semiconductor to the dopant (Advanced Electronic Materials 8, 2100888 (2022)). Therefore, adjusting the EA of the dopant to achieve effective p-doping in conductive polymer semiconductors to pursue high conductivity has become a common practice. However, dopants with high EA content typically have stronger oxidizing properties and are prone to decomposition under environmental conditions (such as exposure to oxygen or moisture). For example, some strong oxidizing dopants may induce oxidative degradation of polymer chains, leading to material structure destruction and reduced polymer structural stability. In addition, high EA dopants may generate free radical intermediates during electron transfer. These reactive species can further induce chain reactions, accelerating the breakage or cross-linking of the polymer backbone, thereby reducing the long-term stability of the material. Moreover, high EA dopants often contain polar groups, which increase the surface energy of the material, making it easier for them to adsorb water molecules. At the same time, in water or humid environments, high EA dopants may catalyze water decomposition reactions, exacerbating electrode corrosion and electrolyte decomposition, thereby reducing the waterproofness of the device. Summary of the Invention

[0005] To address the problems existing in the prior art, the present invention provides a P-type organic semiconductor and its preparation method, thereby solving the technical problem that improving the conductivity of polymers by increasing the EA of dopants leads to a decrease in the stability and water resistance of organic polymer semiconductors.

[0006] This invention is achieved through the following technical solution:

[0007] A method for preparing a p-type organic semiconductor includes the following steps:

[0008] The p-type organic semiconductor is prepared by mixing an organic semiconductor solution, a dopant solution, and an additive solution, and then carrying out a doping reaction at room temperature under a nitrogen atmosphere.

[0009] Preferably, the organic semiconductor includes organic monomers and organic polymers;

[0010] The organic monomers include pyrrole, thiophene, or thiophene derivatives;

[0011] The organic monomer polymers include polypyrrole, polyaniline, polythiophene, polythiophene derivatives, polyacetylene, poly(p-phenylenevinylene), poly(p-phenylene), polyfluorene, P3HT, polycarbazole derivatives, p(g32T-T), p(g32T-TT), DPP4T, PTB derivatives, PffBT4T-2DT, BDT-based polymers, or PIDT-HTBT.

[0012] Preferably, the dopant includes nitroxide radicals, fluorinating agents, oxygen, peroxides, nitrates, iron halides, perhalates, perhalates, persulfates, perborates, hypohalates, halides, perbenzoic acid, or perbenzoic acid derivatives.

[0013] Preferably, the additive includes boron-based Lewis acids, organometallic Lewis acids, rare earth Lewis acids, inorganic acids, cyanide-containing compounds, compounds containing tertiary amine ions, nitro-containing compounds, sulfonic acid-containing compounds, halogen-containing compounds, or tetrafluoroborate.

[0014] Preferably, the concentration of the organic semiconductor solution is 1-100 mg / mL, the molar ratio of the dopant to the aromatic ring in the organic semiconductor is (0.01-10):1, and the molar ratio of the dopant to the additive is (0.1-10):1.

[0015] Preferably, the concentration of the organic semiconductor solution is 5-20 mg / mL, the molar ratio of the dopant to the aromatic ring in the organic semiconductor is (0.03-0.3):1, and the molar ratio of the dopant to the additive is 1:1.

[0016] Preferably, during the doping reaction, the oxygen content in the system is less than 1 ppm and the water vapor content is less than 1 ppm.

[0017] A p-type organic semiconductor is prepared by the method described above.

[0018] A p-type conductive thin film is prepared using the above-mentioned p-type organic semiconductor via solution processing; the conductivity of the p-type conductive thin film is 50–1540 S / cm. -1 The power factor is 7–52 μW / m. -1 K -2The conductivity of the P-type conductive film after being exposed to air for 10 days is 80% to 90% of its initial state; after being immersed in water and dried three times, the conductivity of the P-type conductive film is 60% to 80% of its initial state.

[0019] An electrochromic glass comprises, in sequence, a glass substrate, an ITO transparent electrode, an electrochromic layer, and an electrolyte layer; the electrochromic layer is prepared by solution processing film deposition using a P-type organic semiconductor as described in claim 8; the response time of the electrochromic glass from the colored state to the faded state is 2.1 s.

[0020] Compared with the prior art, the present invention has the following beneficial technical effects:

[0021] This invention proposes a method for preparing a p-type organic semiconductor. In this method, an additive is added to a traditional binary doping system, namely an organic semiconductor + a dopant, to carry out a doping reaction. During the doping reaction, the dopant, the additive, and the organic semiconductor are screened by electron affinity and ionization potential to ensure that the reaction ΔG2 < 0 and ΔG3 < 0. Here, ΔG2 is the Gibbs free energy change value when the additive reacts with the intermediate of the dopant reaction, and ΔG3 is the Gibbs free energy change value of the total reaction. In the reaction, the additive reacts with the reaction intermediates of the dopant, stabilizing the reaction intermediates and ensuring that ΔG2 < 0, resulting in a total Gibbs free energy change of less than 0, thus promoting the forward reaction. In this process, the Gibbs free energy change of the reaction between the organic semiconductor and the dopant is defined as ΔG1. If the reaction between the organic semiconductor and the dopant is spontaneous (ΔG1 < 0), then under the influence of ΔG2, a smaller ΔG3 is obtained, meaning the reaction proceeds more fully in the forward direction. Conversely, if ΔG1 is greater than 0, then under the influence of ΔG2, a ΔG3 less than 0 is obtained, transforming a thermodynamically impossible reaction into a thermodynamically spontaneous one, allowing the reaction to proceed in the forward direction and increasing the concentration of the product. This invention, by introducing additives, regulates the intermediate reaction process, stabilizes the dopant reaction intermediates, and makes the product system more stable, ensuring a fully forward reaction. This strategy not only avoids the instability problem of high EA dopant but also improves doping efficiency through multi-component synergistic effects, providing a new approach for the design of high-performance organic electronic devices. The P-type organic semiconductor in this invention exhibits excellent performance in the fabrication of organic P-type thermoelectric materials and electrochromic devices, and has broad application prospects.

[0022] In addition, this invention also discloses a P-type conductive thin film, which is prepared using the P-type organic semiconductor of this invention and through solution processing. This method is less affected by the processing method and does not require the addition of surfactants to increase solubility. The resulting P-type conductive thin film has a conductivity of 50–1540 S cm⁻¹. -1 It is significantly superior to traditional organic semiconductors, with a power factor of 7–52 μW / m. -1 K -2 The P-type conductive film exhibits excellent thermoelectric conversion capabilities. Furthermore, after 10 days of exposure to air, its conductivity remains at 80%–90% of its initial state, demonstrating strong resistance to oxygen and moisture and good stability. After three cycles of immersion and drying in water, the conductivity remains at 60%–80% of its initial state, indicating good water resistance and structural recovery. Through innovative doping and additive strategies, this P-type conductive film achieves a synergistic improvement in high conductivity, excellent environmental stability (oxygen / water resistance), and thermoelectric performance, overcoming a key bottleneck in the practical application of organic semiconductors and providing a high-performance material foundation for next-generation flexible electronics and energy devices. Attached Figure Description

[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is a schematic diagram illustrating the principle of a method for preparing a p-type organic semiconductor according to the present invention;

[0025] Figure 2 This is a schematic diagram of the four-probe conductivity test after P-type organic semiconductors were processed into films in Examples 3-9;

[0026] Figure 3 The ionization potential of the polymer, the electron affinity of the dopant and additive, and the Gibbs free energy changes of their respective reactions are shown in Example 1 and Comparative Example 1 of this invention.

[0027] Figure 4 The conductivity of P1-D1A1 thin films prepared with different doping molar ratios in Examples 1 to 7;

[0028] Figure 5 The conductivity of P2-D1A1 thin films prepared with different doping molar ratios in Examples 8-14;

[0029] Figure 6The present invention provides a test of the P1-D1A1 film in test 3 being peeled off from the substrate and transferred to a curved / flexible substrate (A) and the change in conductivity after multiple immersion-drying cycles (B).

[0030] Figure 7 The power factor test results of the P-type thermoelectric thin film in test 4 of this invention;

[0031] Figure 8 The results of the air stability test of the P-type conductive film in Test 5 of this invention;

[0032] Figure 9 The results show the change in conductivity of the P-type conductive film in Test 5 of this invention after being stored in air for 10 days, and the stability of P-type conductive polymer films prepared in other studies.

[0033] Figure 10 Demonstration of the process from the colored state to the faded state of the electrochromic glass prepared in Example 1 (A) and the response time (B);

[0034] Figure 11 This is a demonstration of the use of the electrochromic glasses in Example 2 in a real-world setting. Detailed Implementation

[0035] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0036] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0037] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0038] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”

[0039] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0040] Firstly, such as Figure 1 The diagram shown is a schematic representation of the principle of a method for preparing a p-type organic semiconductor according to the present invention.

[0041] Figure 1 The term "primary reaction" refers to a thermodynamically unfavorable or / and difficult reaction to occur; in this invention, it specifically refers to the doping polymerization reaction of organic conductive polymers. Its reactant system mainly consists of organic semiconductors, dopants, and solvents.

[0042] Figure 1 The "coupling reaction" in this invention refers to the transformation of an unfavorable or / and difficult reaction in the "original reaction" into a thermodynamically more readily occurring reaction through the reaction system of this invention. Its reactant system mainly comprises four parts: organic semiconductors, dopants, additives, and solvents.

[0043] Wherein, the electron affinity (EA) of the dopant or additive is less than or equal to the ionization potential (IP) of the organic semiconductor; or, when the EA of the dopant or additive exceeds the IP value of the organic semiconductor, the excess is very small, and the overall reaction still ensures that it proceeds in the forward direction. ΔG is the Gibbs free energy change of the reaction. Using the Gibbs free energy change ΔG to represent the above requirements, then when selecting the organic semiconductor, dopant, and additive, the overall reaction ΔG3 < 0 is achieved, where according to... Figure 1 ΔG3 = ΔG1 + ΔG2, meaning that the addition of the additive makes the overall reaction spontaneous; the product of the reaction system is a conductive polymer solution, and the reaction between the additive and the dopant intermediate is a spontaneous reaction. Figure 1 Since ΔG2 < 0, by introducing ΔG2 less than 0, the change in Gibbs free energy of the overall reaction is controlled, thus obtaining ΔG3 < 0.

[0044] After adding the above-mentioned additives, the intermediate products of the dopant are stabilized, which makes the reaction ΔG2 < 0. Ultimately, the total Gibbs free energy change of the reaction ΔG3 = ΔG1 + ΔG2, ΔG3 < 0, thus realizing the P doping of organic polymers using dopant with a low EA value.

[0045] The organic semiconductor includes organic monomers and organic polymers;

[0046] The organic monomers include pyrrole, thiophene, or thiophene derivatives;

[0047] The organic monomer polymers include polypyrrole, polyaniline, polythiophene, polythiophene derivatives, polyacetylene, poly(p-phenylenevinylene), poly(p-phenylene), polyfluorene, P3HT, polycarbazole derivatives, p(g32T-T), p(g32T-TT), DPP4T, PTB derivatives, PffBT4T-2DT, BDT-based polymers, or PIDT-HTBT.

[0048] Among them, P3HT is poly(3-hexylthiophene), which is a typical organic solar cell donor material;

[0049] The polycarbazole derivative is Poly[N-9′-heptadecanyl-2,7-carbazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)], PCDTBT, with the main chain being an alternating copolymer of carbazole and benzothiadiazole. In addition, the N atom of carbazole is replaced by heptadecanyl.

[0050] p(g32T-T) is Poly(3,3”'-dihexyl-2,2':5',2”:5”,2”'quaterthiophene), i.e., poly[3,3”'-dihexyl-2,2':5',2”:5”,2”'quaterthiophene], a tetraterthiophene composed of 4 thiophene units, connected by alternating 2- and 5-positions. The 3-position of the first thiophene ring is replaced by a hexyl group (3-hexyl), and the 3”' position of the fourth thiophene ring is replaced by a hexyl group (3”'-hexyl).

[0051] p(g32T-TT) is Poly(3,3””'-dihexyl-2,2':5',2”:5”,2”':5”',2””quinquethiophene), i.e., poly[3,3””'-dihexyl-2,2':5',2”:5”,2””pentathiophene], with the main chain being pentathiophene composed of 5 thiophene units;

[0052] The preparation of p(g32T-T) and p(g32T-TT) was carried out in accordance with the references (Nature Materials 18, 149-155 (2019); Advanced Materials 29, 1700930 (2017)), and their molecular weights ranged from 5 to 500 kDa.

[0053] DPP4T is poly(2,5-di(thiophen-2-yl)-3,6-di(2-octyldodecyl)-pyrrolo[3,4-c]pyrrole-1,4-dione-thiophen[3,2-b]thiophene), which contains DPP units and TT units. The DPP unit is diketopyrrolopyrrole, and the TT unit is thieno[3,2-b]thiophene.

[0054] PTB derivatives, including poly([2,6′-4,8-di(5-ethylhexylthiophene)benzo[1,2-b;3,3-b]dithiophene]{3-fluoro-2[(2-ethylhexyl)carbonyl]thiophene[3,4-b]thiophenediyl})(PTB7-Th) or poly[[4,8-bis[(2-ethylhexyl)oxy]-benzo[1,2-B:4,5-B']dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thiophene[3,4-B] thiophene](PTB7); wherein PTB7-Th is a copolymer of benzodithiophene (BDT) and fluorinated thiophene, and compared with PTB7-Th, PTB7 has oxoalkyl side chains instead of thiophene groups.

[0055] PffBT4T-2DT, wherein PffBT4T-2DT(PCE11) is a copolymer of fluorinated benzothiadiazole (BT) and silazine dithiophene;

[0056] BDT-based polymers, wherein the BDT-based polymers include poly[(2,6-(4,8-bis(5-(2-ethylhexyl-3-fluoro)thiophen-2-yl)-benzo[1,2-B:4,5-B']dithiophene])-ALT-(5,5-(1',3'-bis-2-thiophene-5',7'-bis(2-ethylhexyl)benzo[1',2'-C:4',5'-C']dithiophene-4,8-dione)(PM6);

[0057] PIDT-HTBT is poly(indenodithiophene:5,6-b')dithiophene-4,7-bis(4-hexylthiophene-2-yl)benzo[c][1,2,5]thiadiazole, wherein in the poly(indenodithiophene:5,6-b')dithiophene-4,7-bis(4-hexylthiophene-2-yl)benzo[c][1,2,5]thiadiazole, PIDT is indenodithiophene and HTBT is hexylthiophene-benzothiadiazole.

[0058] The dopant is an oxidizing agent, including nitroxide radicals, fluorinating agents, oxygen, peroxides, nitrates, iron halides, perhalates, perhalates, persulfates, perborates, hypohalates, halides, perbenzoic acid or perbenzoic acid derivatives;

[0059] The aforementioned nitrile radicals include TEMPO and MeOTEMPO. + BF4 - TEMPO + BF4 - or NHAcTEMPO + BF4 - ;

[0060] Among them, TEMPO is a 2,2,6,6-tetramethylpiperidine-N-oxy radical, which is a stable nitroxide radical;

[0061] MeOTEMPO + BF4 - BF4 is a 4-methoxy-2,2,6,6-tetramethylpiperidine-N-oxy radical tetrafluoroborate, a derivative of TEMPO, with a methoxy (-OCH3) substituent introduced at the 4-position of the piperidine ring of TEMPO. - For anions.

[0062] TEMPO + BF4 - It is 2,2,6,6-tetramethylpiperidine-N-oxy radical tetrafluoroborate, TEMPO + The TEMPO (2,2,6,6-tetramethylpiperidine-N-oxygen radical) is in its cationic form, and the nitrogen oxide radical is oxidized to an ammonium oxychloride (NO). + ), BF4 - (Tetrafluoroborate) provides charge balance for the anions.

[0063] NHAcTEMPO + BF4 -It is an N-acetoxy-2,2,6,6-tetramethylpiperidine-N-oxy radical fluoroborate, in which an acetoxy (-OAc) substituent is introduced onto the nitrogen atom of TEMPO to form an N-OAc bond, and the anion is BF4. - .

[0064] Fluorination reagents include 1-(chloromethyl)-4-fluoro-1,4-diazoheterocyclic [2.2.2]octane-1,4-tetrafluorodiazo-borate (F-TEDA-BF4, ) or n-fluorobenzenesulfonamide (NFSI);

[0065] Peroxides include hydrogen peroxide, sodium peroxide, potassium peroxide, calcium peroxide, zinc peroxide, or copper peroxide;

[0066] Nitrates include ferric nitrate, zinc nitrate, nickel nitrate, aluminum nitrate, magnesium nitrate, or ammonium nitrate;

[0067] Ferric halides include ferric fluoride, ferric chloride, ferric bromide, or ferric iodide;

[0068] Perhalates include sodium perchlorate, potassium perchlorate, sodium perbromate, potassium perbromate, sodium periodate, or potassium periodate;

[0069] Perhalides include potassium perchlorate, sodium perchlorate, potassium perbromate, sodium perbromate, or magnesium perchlorate;

[0070] Persulfates include sodium persulfate, potassium persulfate, magnesium persulfate, zinc persulfate, ferric persulfate, copper persulfate, or calcium persulfate;

[0071] Hypohalates include sodium hypofluorite, potassium hypofluorite, sodium hypochlorite, potassium hypochlorite, ferric hypochlorite, copper hypochlorite, sodium hypobromite, potassium hypobromite, sodium hypoiodide, or potassium hypoiodide.

[0072] Halite salts include sodium chlorite, potassium chlorite, ferric chlorite, sodium bromite, potassium bromite, sodium iodate, or potassium iodate.

[0073] The additives include boron-based Lewis acids, organometallic Lewis acids, rare earth Lewis acids, inorganic acids, cyanide-containing compounds, tertiary amine cation-containing compounds, nitro-containing compounds, sulfonic acid-containing compounds, halogen-containing compounds, or tetrafluoroborate.

[0074] Among them, boron-based Lewis acids include boron trifluoride (BF3) or tri(pentafluorophenyl)boron (BCF);

[0075] Organometallic Lewis acids include trimethylaluminum;

[0076] Rare earth Lewis acids include lanthanum trifluoride;

[0077] Inorganic acids include sulfuric acid;

[0078] Compounds containing cyano groups, such as 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinone dimethyl ;

[0079] Compounds containing tertiary amine cations, such as 4-acetamide-2,2,6,6-tetramethyl-1-oxepetidine tetrafluoroborate;

[0080] Nitro-containing compounds, such as nitro tetrafluoroborate (BF4NO2);

[0081] Compounds containing sulfonic acid groups, such as bismuth trifluoromethanesulfonate (Bi(OTf)3);

[0082] Halogenated compounds include fluorine-containing compounds or chlorine-containing compounds, wherein the fluorine-containing compounds include copper fluoride (CuF2) and the chlorine-containing compounds include aluminum chloride, zinc chloride, ferrous chloride or copper chloride.

[0083] The solvent includes one or more of water, nitrile solvents, aromatic solvents, alicyclic hydrocarbon solvents, halogenated hydrocarbon solvents, alcohol solvents, ether solvents, ester solvents, sulfone solvents, ketone solvents, and amide solvents, preferably 1,2-dichlorobenzene, 1,1,1,3,3-hexafluoroprop-2-ol (HFIP), or acetonitrile.

[0084] The method for preparing the p-type organic semiconductor specifically includes the following steps:

[0085] At room temperature in a glove box, the organic semiconductor is dissolved in the corresponding solvent, and the dopant and additives are dissolved in the corresponding solvent, preferably acetonitrile, in advance. The three are mixed in proportion and stirred for 1 to 12 hours at room temperature to obtain a P-type organic semiconductor.

[0086] The concentration of the organic semiconductor solution is 1–100 mg / mL, preferably 5–20 mg / mL.

[0087] The molar ratio of the dopant to the aromatic ring in the organic semiconductor is (0.01-10):1, preferably (0.03-0.3):1. The molar ratio of the dopant to the aromatic ring in the organic semiconductor is defined as the doping molar ratio. Fused rings are considered as two or more aromatic rings (e.g., a thieno[3,2-b]thiophene molecule contains two aromatic rings).

[0088] The molar ratio of the dopant to the additive is (0.1 to 10):1, preferably 1:1.

[0089] Secondly, the present invention also discloses a P-type organic semiconductor prepared by the above-described preparation method.

[0090] Thirdly, the present invention also discloses a P-type conductive film prepared using the above-mentioned P-type organic semiconductor. Specifically, the above-mentioned P-type organic semiconductor is prepared by solution processing film formation method. Before preparing the P-type conductive film using solution processing film formation method, the doped polymer solution, i.e. the prepared P-type organic semiconductor solution system, is stirred at room temperature for 1 hour.

[0091] The solution processing film formation method includes, but is not limited to, spin coating, drop coating, scraping coating, spray coating, dip coating, etc., with spin coating or drop coating being preferred.

[0092] The conductivity of the aforementioned P-type conductive film is 50–1540 S cm⁻¹. -1 The power factor is 7–52 μWm. -1 K -2 .

[0093] The P-type conductive film has good air stability; after being exposed to air for 10 days, its conductivity can still be maintained at 80% to 90% of its original state.

[0094] The P-type conductive film has good waterproof performance, can be peeled off in water and transferred to other substrates, and its conductivity can still be maintained at 60% to 80% of its original state after three immersion-drying cycles in water.

[0095] Fourthly, the present invention also discloses an electrochromic glass, comprising a glass substrate, an ITO transparent electrode, an electrochromic layer, and an electrolyte layer in sequence; the electrochromic layer utilizes a P-type organic semiconductor as described above and is prepared by a solution processing film deposition method; the electrochromic glass has a response time of 2.1s from the colored state to the faded state, which is fast.

[0096] Furthermore, in a fifth aspect, the present invention also discloses a smart electrochromic glasses comprising the aforementioned electrochromic glass. By using the electrochromic glass to fabricate smart electrochromic glasses, the light transmittance of the glasses can change from a dark environment to a bright environment under the action of a light sensor.

[0097] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0098] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.

[0099] The following describes the preparation of p-type organic semiconductors using p(g32T-T) and p(g32T-TT) as organic semiconductors, F-TEDA-BF4 and NFSI as dopants, BF3 and BCF as additives, and HFIP and acetonitrile as solvents, to illustrate the technical solution and effects of the present invention.

[0100] Specifically, polymers p(g32T-T) and p(g32T-TT) were dissolved in HFIP to form 13 mg / mL solutions. -1 Solutions of dopant and additives of different concentrations were prepared by dissolving F-TEDA-BF4, NFSI, BF3, and BCF in acetonitrile. Organic semiconductor solutions were then mixed with dopant and additive solutions of different concentrations at different molar doping ratios to obtain organic semiconductor-dopant-additive solutions. All operations and reactions were carried out in a nitrogen-filled glove box (where O2 < 1 ppm and H2O < 1 ppm). The doping molar ratio corresponds to the molar ratio of dopant molecules to aromatic rings in the organic semiconductor; fused rings are counted as two aromatic rings. Unless otherwise specified, the molar ratio of dopant to additive is 1:1.

[0101] For convenience, P, D, and A are used to refer to the organic semiconductor, dopant, and additive in the reactants, respectively. P1, P2, D1, D2, A1, and A2 refer to p(g32T-T), p(g32T-TT), F-TEDA-BF4, NFSI, BF3, and BCF, respectively.

[0102] Example 1

[0103] A p-type organic semiconductor, P1-D1A1, was prepared using organic semiconductor p(g32T-T), dopant F-TEDA-BF4, and additive BF3. In this embodiment, D1:P1 = 0.1:1, meaning the molar ratio of the dopant to the aromatic ring in the organic semiconductor (doping molar ratio) is 0.1:1, and D1:A1 = 1:1, meaning the molar ratio of the dopant to the additive is 1:1.

[0104] Comparative Example 1

[0105] The difference from Example 1 is that no additives were added during the reaction process. That is, a P-type organic semiconductor was prepared by organic semiconductor p(g32T-T) and dopant F-TEDA-BF4. The product is referred to as P1-D1.

[0106] Example 2

[0107] The difference between this embodiment and Embodiment 1 is that the doping molar ratio is 0.03.

[0108] Example 3

[0109] The difference between this embodiment and Embodiment 1 is that the doping molar ratio is 0.05.

[0110] Example 4

[0111] The difference between this embodiment and Embodiment 1 is that the doping molar ratio is 0.07.

[0112] Example 5

[0113] The difference between this embodiment and Embodiment 1 is that the doping molar ratio is 0.15.

[0114] Example 6

[0115] The difference between this embodiment and Embodiment 1 is that the doping molar ratio is 0.2.

[0116] Example 7

[0117] The difference between this embodiment and Embodiment 1 is that the doping molar ratio is 0.3.

[0118] Example 8

[0119] The difference between this embodiment and Embodiment 1 is that the organic semiconductor is p(g32T-TT) and the doping molar ratio is 0.1.

[0120] Example 9

[0121] The difference between this embodiment and Embodiment 8 is that the doping molar ratio is 0.03.

[0122] Example 10

[0123] The difference between this embodiment and Embodiment 8 is that the doping molar ratio is 0.05.

[0124] Example 11

[0125] The difference between this embodiment and Embodiment 8 is that the doping molar ratio is 0.07.

[0126] Example 12

[0127] The difference between this embodiment and Embodiment 8 is that the doping molar ratio is 0.15.

[0128] Example 13

[0129] The difference between this embodiment and Embodiment 8 is that the doping molar ratio is 0.2.

[0130] Example 14

[0131] The difference between this embodiment and Embodiment 8 is that the doping molar ratio is 0.3.

[0132] Example 15

[0133] The difference between this embodiment and Embodiment 1 is that the additive is BCF, and the resulting P-type organic semiconductor is denoted as P1-D1A2.

[0134] Example 16

[0135] The difference between this embodiment and Embodiment 1 is that the dopant is NFSI, and the resulting P-type organic semiconductor is denoted as P1-D2A1.

[0136] Example 17

[0137] The difference between this embodiment and Embodiment 1 is that the dopant is NFSI, the additive is BCF, and the resulting P-type organic semiconductor is denoted as P1-D2A2.

[0138] Example 18

[0139] The difference between this embodiment and Embodiment 8 is that the additive is BCF, and the obtained P-type organic semiconductor is represented as P2-D1A2.

[0140] Test 1: Calculation of the Gibbs free energy change of the reaction

[0141] Figure 3 The ionization potential, electron affinity of dopants and additives, and Gibbs free energy changes of their respective reactions in Embodiment 1 and Comparative Example 1 of this invention were calculated using density functional theory (DFT). Specifically, the ionization potential (IP), electron affinity (EA) of dopants and additives, and Gibbs free energy changes (ΔG) of the doping reactions in Embodiment 1 and Comparative Example 1 were calculated. The ionization potential of P1 and the electron affinity of D1 and A1 were obtained through these calculations. Furthermore, the ΔG of the doping reactions P1-D1 and P1-D1A1 were also obtained. Figure 3As shown, the ΔG for the doping reaction P1-D1 is -165.1 kJ / mol, and the ΔG for the doping reaction P1-D1A1 is -355.2 kJ / mol. Both reactions have negative ΔG values, proving that they can proceed spontaneously. However, the coupled reaction with additive A1 has a larger |ΔG1|. According to the formula ΔG = -RTlnK, a larger |ΔG1| will lead to an increase in the chemical equilibrium constant K. The chemical equilibrium constant K, in turn, depends on the concentration changes of reactants and products (K0). P1-D1 =[P1 + D1 - ] / [P1][D1],K P1-D1A1 =[P1 + D1 - The process of generating P1-D1A1 films (-A1] / [P1][D1][A1]) ultimately leads to higher product concentrations, promoting a rightward shift in chemical equilibrium. Introducing this mechanism significantly improves the conductivity of the films, resulting in a conductivity of 334 S / cm for the P1-D1 film and 1540 S / cm for the P1-D1A1 film.

[0142] Test 2: Conductivity Test

[0143] The P-type organic semiconductors obtained in Examples 1-14 of this invention were deposited on a glass substrate by spin coating to prepare polymer thin films, and their conductivity was tested. Specifically, the glass substrate was first cleaned in an ultrasonic bath with detergent solution, isopropanol, and acetone, respectively, and then dried with nitrogen gas. Before spin coating, the glass substrate was treated with oxygen plasma for 5 minutes, and then the glass substrate was transferred to a glove box. Thin films were obtained by spin coating using the P-type organic semiconductors obtained in Examples 1-14 (2000 rpm, 60 s). The obtained thin films were further dried in a glove box for 12 hours to form a final film.

[0144] Conductivity testing of conductive thin films prepared using the p-type organic semiconductors obtained in Examples 1-14 of this invention was performed by transferring the conductive thin film samples into a thermoelectric testing instrument (NETZSCH SBA-458, Germany) and using the four-probe method. Figure 2 The sheet resistance was tested to obtain its conductivity. The test results are shown in [reference needed]. Figures 4-5 ,in:

[0145] Figure 4 The figures show the conductivity of P1-D1A1 thin films prepared with different doping molar ratios in Examples 1 to 7. As can be seen from the figures, under the premise of fixing D1:A1 = 1:1, by changing the molar doping ratio of D1 to P1, the conductivity is the highest when the doping molar ratio is 0.1:1.

[0146] Figure 5The figures show the conductivity of P2-D1A1 films prepared with different doping molar ratios in Examples 8 to 14. As can be seen from the figures, under the premise of fixing D1:A1 = 1:1, by changing the molar doping ratio of D1 to P2, the conductivity is the highest when the doping molar ratio is 0.1:1.

[0147] Test 3: Transferability and Water Resistance Test

[0148] Using the P1-D1A1 organic semiconductor obtained in Example 1 as an example, a P-type conductive thin film was prepared to verify the film's transferability and water resistance. Specifically, the glass substrate was cleaned in advance with detergent solution, isopropanol, and acetone in an ultrasonic bath, and then dried with nitrogen gas. Before spin coating, the glass substrate was treated with oxygen plasma for 5 minutes, and then the glass substrate was transferred to a glove box to obtain the thin film by spin coating (2000 rpm, 60 s). The thin film was further dried in the glove box for 12 hours to form the film; subsequently, the glass substrate coated with the film was immersed in deionized water for a period of time to separate the film from the substrate, and the detached film could be transferred to curved glass or a flexible substrate. The conductivity at different immersion times was obtained by repeating the immersion and drying cycle, and the test results are as follows. Figure 6 As shown.

[0149] Figure 6 The figures show the changes in conductivity of the P1-D1A1 film after being peeled from the substrate and transferred to a curved / flexible substrate (A) and after multiple immersion-drying cycles (B) in Test 3 of this invention. As can be seen from the figures, the P1-D1A1 film has high waterproof performance and transferability.

[0150] Test 4: Power factor test of P-type thermoelectric thin films prepared from P-type organic semiconductors

[0151] Using the P-type organic semiconductors prepared in Examples 15-18 of this invention, P-type conductive thin films were fabricated, and their power factors were tested, specifically as follows:

[0152] The P-type organic semiconductor prepared in the above examples was used to prepare a P-type conductive film. The glass substrate was cleaned in an ultrasonic bath with detergent solution, isopropanol, and acetone, respectively, and then dried with nitrogen. Before use, the substrate was bombarded with plasma for 5 minutes using a plasma cleaner. The glass substrate was then transferred to a glove box for spin coating, and the film was further dried in the glove box for 12 hours to form the final film. The sample was then transferred to a thermoelectric analyzer (NETZSCH SBA-458, Germany) for Seebeck coefficient determination at room temperature under argon protection. Finally, the formula PF = S was used. 2 σ is used to obtain the power factor, where PF is the power factor, S is the Seebeck coefficient, and σ is the conductivity. The test results are as follows: Figure 7 As shown, Figure 7The figure shows the power factor test results of the P-type conductive thin film in Test 4 of this invention. As can be seen from the figure, different doping molar ratios and types of organic semiconductors result in different power factors. When the ratio of additive to dopant is fixed and the dopant molar ratio is 0.07, the highest power factor (PF) in P1-D1A1 is 54 μW / m. -1 K -2 .

[0153] Test 5: Air stability test

[0154] The P1-D1A1 organic semiconductor obtained in Example 1 was used to prepare a conductive thin film by spin coating. The film was then placed in air at room temperature for ten days to verify its air stability. The conductivity of the film was measured and recorded on days 0-10. The test results are shown below. Figure 8 , Figure 8 The figure shows the air stability test results of the P-type conductive film in Test 5 of this invention. As can be seen from the figure, the P1-D1A1 film prepared by this invention can still maintain 90% of its original conductivity after 10 days of air exposure. Meanwhile, the air stability was compared with that of other P-type films prepared by different processes; the comparison results are shown in the figure. Figure 9 , Figure 9 The figure shows the change in conductivity of the P-type conductive film in Test 5 of this invention after being stored in air for 10 days, and the stability of the P-type conductive polymer film prepared in other studies. As can be seen from the figure, the air stability of the conductive polymer film prepared in this invention is better than that of other conductive polymers.

[0155] Preparation Example 1: Preparation of Electrochromic Glass Using P-type Organic Semiconductors

[0156] Electrochromic glass was prepared using the P-type organic semiconductor obtained in Example 1 of this invention, thereby demonstrating that the prepared P-type organic semiconductor is also suitable for the printing and preparation of large-area electrochromic glass.

[0157] Specifically, the electrochromic device in this preparation example mainly consists of a transparent glass substrate, an ITO transparent electrode layer, an electrochromic layer, and a transparent electrolyte layer. The ITO glass is a commonly available commercially available conductive glass. Before coating, the cleaned and dried ITO glass was bombarded with plasma for 5 minutes in a plasma etching apparatus. Subsequently, a P-type organic semiconductor was spin-coated onto the conductive glass to form an electrochromic layer. Then, a polymer electrolyte was prepared according to the ratio of LiClO4 (1.5g), propylene carbonate (10mL), and PMMA powder (10g). A certain amount of the prepared electrolyte was deposited onto the previously spin-coated ITO glass, and a new ITO glass was placed on top. A small amount of pressure was applied, and the device was left to stand overnight to obtain the electrochromic glass. The response process of the prepared electrochromic glass and the switching response time of the device are as follows: Figure 10 As shown. Figure 10To demonstrate the process of preparing the electrochromic glass obtained in Example 1 from the colored state to the bleached state (A) and the response time (B), it can be seen from the figure that when the device changes from the oxidized state (bleached state) to the reduced state (colored state), the transmittance decreases significantly and the shortest response time is about 4.3s; conversely, the shortest response time is about 2.1s.

[0158] Preparation Example 2: Preparation of Electrochromic Glasses from Electrochromic Glass

[0159] The electrochromic glass device prepared in Example 1 was further processed into electrochromic glasses. Specifically, electrode wires were connected and led out from both sides of ITO conductive glass, and two electrochromic glass pieces of the same size were mounted on a self-made or commercially available eyeglass frame. The electrode wires were connected in series, and a photosensor and a commercially available power battery were connected to the circuit. The photosensor acts as a light switch (when there is sufficient light, the circuit is turned on, and the device changes to a colored state to block light from entering; when there is insufficient light, it provides a reverse circuit, and the device changes to a faded state to allow a large amount of light to enter). Figure 11 To demonstrate the electrochromic glasses prepared in Example 2 under real-world conditions, as shown in the figure, under sufficient indoor lighting, the photodetector detects a large amount of light, the circuit applies a voltage to both sides of the electrodes, and the device enters the colored state. Conversely, when the photodetector is covered by hand, the device enters the decolored state.

[0160] Example 19

[0161] The difference between this embodiment and Embodiment 1 is that the organic semiconductor is pyrrole, the dopant is TEMPO, and the additive is trimethylaluminum.

[0162] Example 20

[0163] The difference between this embodiment and Embodiment 1 is that the organic semiconductor is polyaniline, the dopant is TEMPO, and the additive is lanthanum trifluoride.

[0164] Example 21

[0165] The difference between this embodiment and Embodiment 1 is that the organic semiconductor is PIDT-HTBT, the dopant is TEMPO, and the additive is sulfuric acid.

[0166] Example 22

[0167] The difference between this embodiment and Embodiment 20 is that the organic semiconductor is polypyrrole, the dopant is hydrogen peroxide, and the additive is 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinone dimethyl ether.

[0168] Example 23

[0169] The difference between this embodiment and Example 20 is that the organic semiconductor is polypyrrole, the dopant is ferric nitrate, and the additive is 4-acetamide-2,2,6,6-tetramethyl-1-oxependyridine tetrafluoroborate.

[0170] Example 24

[0171] The difference between this embodiment and Embodiment 20 is that the organic semiconductor is polypyrrole, the dopant is iron fluoride, and the additive is nitric tetrafluoroborate.

[0172] Example 25

[0173] The difference between this embodiment and Embodiment 21 is that the organic semiconductor is polypyrrole, the dopant is sodium perchlorate, and the additive is bismuth trifluoromethanesulfonate.

[0174] Example 26

[0175] The difference between this embodiment and Embodiment 21 is that the organic semiconductor is polypyrrole, the dopant is potassium perchlorate, and the additive is copper fluoride.

[0176] Example 27

[0177] The difference between this embodiment and Embodiment 21 is that the organic semiconductor is polypyrrole, the dopant is sodium persulfate, and the additive is aluminum chloride.

[0178] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a p-type organic semiconductor, characterized in that, Includes the following steps: The p-type organic semiconductor is prepared by mixing an organic semiconductor solution, a dopant solution, and an additive solution, and then carrying out a doping reaction at room temperature under a nitrogen atmosphere.

2. The method for preparing a p-type organic semiconductor according to claim 1, characterized in that, The organic semiconductor includes organic monomers and organic polymers; The organic monomers include pyrrole, thiophene, or thiophene derivatives; The organic monomer polymers include polypyrrole, polyaniline, polythiophene, polythiophene derivatives, polyacetylene, poly(p-phenylenevinylene), poly(p-phenylene), polyfluorene, P3HT, polycarbazole derivatives, p(g32T-T), p(g32T-TT), DPP4T, PTB derivatives, PffBT4T-2DT, BDT-based polymers, or PIDT-HTBT.

3. The method for preparing a p-type organic semiconductor according to claim 1, characterized in that, The dopants include nitroxide radicals, fluorinating agents, oxygen, peroxides, nitrates, iron halides, perhalates, perhalates, persulfates, perborates, hypohalates, halideates, perbenzoic acid, or perbenzoic acid derivatives.

4. The method for preparing a p-type organic semiconductor according to claim 1, characterized in that, The additives include boron-based Lewis acids, organometallic Lewis acids, rare earth Lewis acids, inorganic acids, cyanide-containing compounds, tertiary amine cation-containing compounds, nitro-containing compounds, sulfonic acid-containing compounds, halogen-containing compounds, or tetrafluoroborate.

5. The method for preparing a p-type organic semiconductor according to claim 1, characterized in that, The concentration of the organic semiconductor solution is 1–100 mg / mL, the molar ratio of the dopant to the aromatic ring in the organic semiconductor is (0.01–10):1, and the molar ratio of the dopant to the additive is (0.1–10):

1.

6. The method for preparing a p-type organic semiconductor according to claim 1, characterized in that, The concentration of the organic semiconductor solution is 5–20 mg / mL, the molar ratio of the dopant to the aromatic ring in the organic semiconductor is (0.03–0.3):1, and the molar ratio of the dopant to the additive is 1:

1.

7. The method for preparing a p-type organic semiconductor according to claim 1, characterized in that, During the doping reaction, the oxygen content in the system is less than 1 ppm and the water vapor content is less than 1 ppm.

8. A p-type organic semiconductor, characterized in that, It is prepared by the method described in any one of claims 1 to 7.

9. A P-type conductive thin film, characterized in that, The p-type conductive film is prepared by solution processing using a p-type organic semiconductor as described in claim 8; the conductivity of the p-type conductive film is 50–1540 S / cm. -1 The power factor is 7–52 μW / m. -1 K -2 ; After being exposed to air for 10 days, the conductivity of the P-type conductive film is 80% to 90% of its initial state; after being immersed in water and dried three times, the conductivity of the P-type conductive film is 60% to 80% of its initial state.

10. An electrochromic glass, characterized in that, The electrochromic glass comprises a glass substrate, an ITO transparent electrode, an electrochromic layer, and an electrolyte layer. The electrochromic layer is prepared by solution processing of a P-type organic semiconductor as described in claim 8. The response time of the electrochromic glass from the colored state to the faded state is 2.1 s.